(untitled) (Research, Society and Development, 2020)
The objective of this study was to identify whether there is a relationship between engagement and flourishing in the work of the employees of Hospital Alpha located in the Northwest Region of the State of Rio Grande do Sul. of development, a progressive state of satisfaction and well-being at work, while engagement at work refers to a situation of satisfaction with the activities carried out. These themes are still little explored together, but they are relevant in the context of the work. We conducted a survey with the Hospital Alpha team. Data collection was performed using a research instrument that was divided into three parts. Data analysis and interpretation was performed using the SPSS® Software. The sample was classified as flowering, showing no index of low flowering, only medium and high. In the aspect of engagement at work, only the absorption dimension had a low index. In general, Hospital Alpha professionals have medium and high levels of engagement. This new way of analyzing individuals and the organizational environment, called engagement and flourishing, can be used as an organization strategy to carry out activities in different areas of organizations.